2010
DOI: 10.3109/15563650.2010.488640
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute complicated glyphosate intoxication in the emergency department

Abstract: The results of this study showed that age > 50 years, X-ray abnormalities, and ALT > 40 U/L were significant predictive factors for complications in patients with glyphosate surfactant herbicide poisoning; patients with these findings might require admission to the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 27 publications
1
36
1
1
Order By: Relevance
“…(15) When healthy American adults were tested using a chemical container with a 1.5-cm diameter, the mean maximum sip volumes were 14.9 mL for men and 14.3 mL for women, which were smaller than the volumes measured when using a cup. (14) In contrast, although containers with a 2.6-cm internal diameter were used in the present study, the poisoning agent sip amounts were 30.00 ± 15.28 mL for health care providers and 26.46 ± 12.76 mL for non-practitioners, which were higher than the results of the previous study (table 2). The poisoning agent mouthful amounts were 60.09 ± 17.28 mL for health care providers and 59.63 ± 20.17 mL for non-practitioners.…”
Section: Liquid Medicinecontrasting
confidence: 56%
See 1 more Smart Citation
“…(15) When healthy American adults were tested using a chemical container with a 1.5-cm diameter, the mean maximum sip volumes were 14.9 mL for men and 14.3 mL for women, which were smaller than the volumes measured when using a cup. (14) In contrast, although containers with a 2.6-cm internal diameter were used in the present study, the poisoning agent sip amounts were 30.00 ± 15.28 mL for health care providers and 26.46 ± 12.76 mL for non-practitioners, which were higher than the results of the previous study (table 2). The poisoning agent mouthful amounts were 60.09 ± 17.28 mL for health care providers and 59.63 ± 20.17 mL for non-practitioners.…”
Section: Liquid Medicinecontrasting
confidence: 56%
“…(12) At present, the poisoning amounts in a Korean study of agricultural chemical intoxication were calculated by multiplying the patient-reported number of swallows by the estimated sip amount (20-30 mL). (13,14) To create a situation similar to actual agricultural chemical poisoning, a medicine bottle with a 2.6-cm internal diameter, which is similar to the sizes of agricultural chemical bottle openings, was used in the present study. Previous studies were performed using liquids contained in cups; however, agricultural chemicals and other industrial liquids are contained in special containers with internal diameters smaller than that of a cup, and toxicologically, the tastes of these chemicals differed from that of water.…”
Section: Liquid Medicinementioning
confidence: 99%
“…The kidney may also be an organ for excretion of GPSH components (Moon and Chun, 2010;Roberts et al, 2010;Sribanditmongkol et al, 2012). Thus, early evidence of kidney injury could be used to predict the risk of a fatal outcome in GPSH toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early evidence of kidney injury could be used to predict the risk of a fatal outcome in GPSH toxicity. Plasma (pCr) or serum creatinine (sCr) and blood urea nitrogen (BUN) have usually been used as indicators, or biomarkers, for kidney injury in human GPSH intoxication (El-Shenawy, 2009;Lee et al, 2008;Moon and Chun, 2010;Talbot et al, 1991;Tominack et al, 1991). Recently, several studies have suggested that pCr is not sensitive enough to detect early kidney injury or predict subsequent functional change (Sherwin et al, 2012;Toto, 1995;Vaidya et al, 2008b;Woitas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Korea from 2010 involving 76 patients who ingested glyphosate formulations revealed respiratory failure, hypotension, acute pancreatitis, acute kidney injury, hyperkalemia and seizures as common symptoms [60]. A study involving over 600 patients with acute poisoning from glyphosate-containing herbicides in two hospitals in Sri Lanka between 2002 and 2007 found a 3.2% fatality rate, with a median time to death of 20 hours [61].…”
Section: Discussionmentioning
confidence: 99%